Socioeconomic school segregation as a dimension of educational exclusion: Fifteen years of evolution in Latin America - Natalia Krüger (Arizona State University, 2019)
The massification of Latin American educational systems leads to a reconsideration of the concept of educational inclusion/exclusion since, partly, social disadvantages have been transferred inside the school, configuring situations of unequal inclusion. Considering three main dimensions of educational inclusion - access, learning and integration/segregation - this paper focuses on the latter, since it has been the least studied in the region. The aim is to empirically analyze the current situation, the dynamics and the evolution of socioeconomic segregation in the secondary school system during the last decades. To this end, information from the 2000-2015 rounds of the Programme for International Student Assessment (PISA) corresponding to nine Latin American countries is used. Various synthetic indices are estimated to quantify and characterize the problem, comparing the region with others, as well as the Latin American countries with each other. The results suggest that the region presents the lowest levels of social integration at school, in spite of a certain reduction of the segregation levels during the last years. Given the intensity of the problem and its potential impact on inequality of opportunities, the ultimate goal of this study is to contribute to the visualization of the issue and to provide information for the design of policies.